How Policies are Shaping Longer-Lasting Textiles in Europe - Bhatnagar, Anubhuti; Manivannan, Arun Chandra; Niinimäki, Kirsi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
European policies are evolving to extend the lifespan of textiles and reduce waste, but challenges remain in implementation. This study examines how policies have shifted from voluntary measures before 2020 to stricter regulations, such as the Eco-design for Sustainable Products Regulation and Extended Producer Responsibility schemes. While these policies aim to make textiles more durable, most still focus on managing waste rather than preventing it. A key challenge is the lack of repair infrastructure and inconsistent enforcement across countries. Additionally, current policies sometimes prioritize recyclability over longevity, which can lead to unintended consequences like shorter product lifespans. Policies must better support durability through financial incentives, clearer design standards, and better enforcement to make a real impact. Investing in repair and reuse infrastructure alongside recycling efforts will be essential for creating a genuinely circular textile economy.